Ilha interdisciplinar de racionalidade: uma discussão sobre o funcionamento dos condicionadores de ar na escola - Demarco, Daiana (2018)
The present text is about a study that aims to explore the applicability of the interdiscip linary islands of rationality, in the perspective of scientific and technical literacy and it’s inserted in the research line “Theoretical methodological Fundamentals for teaching science and mathematics”. Studies reveal that, form 1980, the scientific literacy has gained strength in the national scenario, opening a wide range of debates about the science teaching, bringing forth some changes in the educational framework. These studies have shown that scientific literacy contributes to the development of cr itic citizens who are more engaged with society, although it shows lack of studies and the possible inclusion in the school context. This necessity rai ses the question of the study: “How can a study project aimed at problem solving experienced by the students, help the process of scientific literacy?” Therefore, it was chosen the proposal presented by Gerard Fourez, named “Interdisciplinary islands of rationality”. Aiming to reach the objective, this is to favor teaching through projects that promote technical and scientific literacy. The study was carried out with a class of 21 students of third year high school at Jesus Maria Jose’s in Palmeira das Missões – RS. The main purpose of this study is to build an interdisciplinary island of rationality and value its efficiency as a promoter of the technical and scientific literacy as seen by Fourez. The proposal was developed in 14 meetings where it was applied a project of problem solving situation related to the school’s reality, which was the installation and operation of air conditioning devices in the school. The research developed to evaluate the developed activity and its contribution to the process of scientific literacy of the students, was conducted as a qualifying action- research, students used a data diary and an observation sheet to collect data. The center of attention was kept in the attributes mentioned by Fourez (1997) as part of the technical scientific literacyIndependence, domain and communication. The results reached have indicatives of the developed project’s validation and its contribution for the scientific literacy process of the student’s enrolled, specially related to abilities in communication and independence. This way, the highlights of the studies are related to the negotiation between the components of the study groups, the consultation with the specialists selected through the identification of the “black boxes” that should be opened in the study, the knowledge of expressing opinions during the decision making, and the student’s ability of arguing about their choices. Such aspects related to others as the creativity, search for information and knowing how to do things, gave the base for the discussion about the potentiality of the developed study. As an educational product, the study presented a support material for teachers that is available with free access. For the formulation of the material takes as referential the studies used in the elaboration of this dissertation and turns to a didactic dialogue enrolling the aspects considered important at the moment of the operationalization of an IIR that could subsid the actions of teachers in the basic education.